La hija natural - Tonos, Leticia; Rodríguez, Julietta; Checho, Víctor; Ramos, Andrés (Línea Espiral Producciones : Isla Films, 2011)
"Maria, 18 year old daughter of a single mother, decides to look for the father she has never met after her mother dies in a tragic accident. She finally finds him in a nearby town, living in what appears to be a haunted old country house in the middle of a neglected banana plantation. Amidst the peculiarities and superstitions of the Dominican country side, father and daughter will have to face the ghosts of the past that haunt them both."--